1
$\begingroup$

I am reading this article.
The model hamiltonain of 2D square lattice for spinless fermions is written as:
$$H=H_{kin}+H_{int}=-\frac{J}{2}\sum_{<n,m>}c_n^\dagger c_m+\frac{V}{2}\sum_{<n,m>}n_nm_m$$ with J=hopping, V=interaction potential, $<n,m>$ nearest neighbor pairs and $n_n=c_n^\dagger c_n$=Number operator.
Baeriswyl wavefunction (BWF) can be written as:
$$|\psi_B>=N_B^{-1}\exp{(\tilde{\alpha}H_{kin})}|CDW>$$ and expression for CDW in k-space can be written as: $$|CDW>=\Pi_{k\epsilon RBZ}\frac{1}{\sqrt{2}}(c_k^\dagger +c_{k-Q}^\dagger)|0>$$ If we convert H into k-space also we will get something like this: $$H_{kin}=\sum_k\epsilon(k)c_k^\dagger c_k$$ $$H_{int}=-\frac{V}{N}\sum_{k,k',q}\epsilon(k)c_{k+q}^\dagger c_k c_{k'-q}^\dagger c_{k'}$$ To get final expression for $|\psi_B>$ (equ.3 in mentioned article) one have to apply $e^{\tilde{\alpha}H_{kin}}$ on $|CDW>$. I tried to solve this but couldn't succeed. Can anyone help me in this?


My Attempt

$$|\psi_B>=\Pi_{k\epsilon RBZ}\frac{N_B^{-1}}{\sqrt{2}} \exp{[\tilde{\alpha}{\sum_k\epsilon(k)c_k^\dagger c_k}]}(c_k^\dagger +c_{k-Q}^\dagger)|0>$$

$$|\psi_B>=\Pi_{k\epsilon RBZ}\frac{N_B^{-1}}{\sqrt{2}} [\exp{[\tilde{\alpha}{\sum_k\epsilon(k)c_k^\dagger c_k}]}c_k^\dagger |0> +\exp{[\tilde{\alpha}{\sum_k\epsilon(k)c_k^\dagger c_k}]}c_{k-Q}^\dagger)|0>]$$ In the article they are saying that this is equal to $$|\psi_B>=\Pi_{k\epsilon RBZ}\frac{N_B^{-1}}{\sqrt{2}} [\exp{[\tilde{\alpha}{\sum_k\epsilon(k)}]}c_k^\dagger |0> +\exp{[\tilde{\alpha}{\sum_k\epsilon(k)}]}c_{k-Q}^\dagger)|0>]$$ But how?

$\endgroup$
0
$\begingroup$

$H_{kin}$ can be written as: $$\begin{bmatrix}c_k^\dagger & c_{k-\pi}^\dagger\end{bmatrix}\begin{bmatrix}\epsilon(k) & 0 \\0 & \epsilon(k- \pi)\end{bmatrix}\begin{bmatrix}c_k \\ c_{k-\pi}\end{bmatrix}$$ and $\epsilon(k-\pi)=-2*t*\cos(k-\pi)=2*t*\cos k=-\epsilon(k)$ and at half-filling $Q=\pi$. As $c_k^\dagger$ and $c_{k-\pi}^\dagger$ are eigenstates of $H_{kin}$ so one can write $\exp(\alpha H_{kin})(c_k^\dagger+c_{k-\pi}^\dagger)=\exp(\alpha \epsilon(k))c_k^\dagger+\exp(-\alpha \epsilon(k))c_{k-\pi}^\dagger$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.